Factors that influence Intermediate Intensive English I students in their performance of the listening skill at the Foreign Language Department of the University of El Salvador, semester II, 2015. - Hernández Pineda, Patricia Beatriz
This qualitative study was carried out with the objective of investigating the internal and external factors that were influencing Intermediate Intensive English I students in their performance of listening skill. The participants were four groups of the students already mentioned from the Foreign Language Department of the University of El Salvador. The data were gathered through a diagnostic test, open ended questionnaire and non-participant observations. Findings revealed that among internal and external factors affecting students' listening performance are: motivation, lack of vocabulary, lack of background knowledge, anxiety, lack of concentration, type of passage, authenticity, noise and distortion, speech rate, speakers' accent and environmental noises. As a result it was clearly evident that these factors are deeply implied in the development of the students listening performance.